(untitled) (Canadian Medical Education Journal, 2025)
Implication statement Rural and remote physicians face challenges including management of critically ill patients. At eleven British Columbia resident teaching sites, seven of which were rural, we developed interactive video simulation sessions for treating such patients, and these were video-preceptored by a remotely located physician providing real-time debriefing. Family medicine residents found this program acceptable and educational, felt it increased confidence in managing sick patients, and could lead to future rural experiences and retention. Given this program additionally decreases cost and time of simulations due to less travel, we anticipate similar benefits for other Canadian family medicine programs.